EFFECTS OF INTELLECTUAL CAPITAL ON THE FINANCIAL PERFORMANCE IN BRAZILIAN COMPANIES AND CHILEAN - Turra, Salete; Vergini, Danielle Paná; Jacomossi, Fellipe André; Hein, Nelson (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
The objective of the research was to investigate the influence of intellectual capital measured by the Intellectual Capital Value Added (VACI) on financial performance in Brazilian and Chilean companies in 2013. We conducted a descriptive, documentary, with a quantitative approach through statistical canonical correlation technique. Data were collected in the Tomnson® database. The results of the study showed existing canonical correlation between the variables that make up the VACI with the financial performance variables in Brazil and Chile. Thus, it was concluded that the intellectual capital significantly influences the financial performance of the Brazilian and Chilean companies.